An unusual case of septate uterus with double cervix and longitudinal vaginal septum simulating uterus didelphys - Vijay, Alka; Salve, Archana; Murdia, Kshitij; Chandra, Vipin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Rare mullerian anomalies not falling in any present classification are sometimes reported. A 27-year‐old woman came to our hospital with history of secondary infertility. She was found to have a longitudinal vaginal septum, cervical duplication and two endometrial cavities, separated by a complete septum. Laparoscopic examination revealed a relatively intact uterine fundus with both patent fallopian tubes. Hysteroscopic exam confirmed the presence of double vagina and double cervix, as well as complete uterine septum. It was a rare variant of complete septate uterus with double cervix, which could be successfully treated by hysteroscopic operation. Diagnosis and management of this unusual Müllerian anomaly are discussed in the context of a literature review.